1995
DOI: 10.1063/1.360489
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic resonance study on Fe-SiO2 granular films

Abstract: Ferromagnetic resonance (FMR) measurement was performed at the frequency of 9.8 GHz and at the room temperature on a series of Fe-SiO2 granular films fabricated by the Ar+-beam sputtering technique. Our results indicated that when the iron volume fraction (fv) of the films exceeds 0.28, the FMR spectra are superpositions of volume modes and surface modes. The analysis on the effective anisotropy field suggests that the intrinsic anisotropy (including the volume and interface one) becomes maximal when fv near t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…However, for systems with an inhomogeneous magnetization, as expected for well-faceted nanocrystals with a large lattice mismatch at the particle-support interface, [14] the excitation of other spin states becomes possible. [15,16] The high-field resonance, whose position strongly depends on gas adsorption, can be attributed to a surface mode, which is very sensitive to changes in the boundary conditions at the surface of the particle. The intensity of this resonance decreases strongly if the orientation of the static magnetic field deviates from the perpendicular orientation with respect to the surface.…”
mentioning
confidence: 99%
“…However, for systems with an inhomogeneous magnetization, as expected for well-faceted nanocrystals with a large lattice mismatch at the particle-support interface, [14] the excitation of other spin states becomes possible. [15,16] The high-field resonance, whose position strongly depends on gas adsorption, can be attributed to a surface mode, which is very sensitive to changes in the boundary conditions at the surface of the particle. The intensity of this resonance decreases strongly if the orientation of the static magnetic field deviates from the perpendicular orientation with respect to the surface.…”
mentioning
confidence: 99%
“…In general, in this crystal structure there exist vacancies in both the cation and anion sublattices. Moreover, those studies showed that the defect chemistry can be described with a cluster model, where cation and anion vacancies may not only be randomly distributed but also form more complex defectsmesoscopic cluster-type inhomogeneities [6,26,27]. The surface chemical segregation phenomena were observed in rare-earth doped manganites [28][29][30][31].…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…The same FMR linewidth broadening effect and a sharp increase in DH with a decreasing concentration of nanoparticles were noted in Refs. [27][28][29]. The explanation of the observed dependences of magnetic losses is based on the model of the spin-polarized relaxation (SPR) developed in Ref.…”
Section: Article In Pressmentioning
confidence: 99%